Climate change and the World Bank group (The World Bank (WB), 2009)
Climate change threatens to derail development, even as development pumps ever-greater quantities of carbon dioxide into an atmosphere already polluted with two centuries of Western emissions. The World Bank, with a newly-articulated Strategic Framework on Development and Climate Change, must confront these entangled threats in helping its clients to carve out a sustainable growth path. This evaluation assesses the Bank's experience with key win-win policies in the energy sector.